2007
DOI: 10.1021/es062874c
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Stability of Organic Carbon-Stimulated Chromate Reduction in Contaminated Soils and Its Relation to Manganese Redox Status

Abstract: In-situ reduction of toxic Cr(V1) to less hazardous Cr(II1) is becoming a popular strategy for remediating contaminated soils. However, the long term stability of reduced Cr remains to be understood, especially given the common presence of MnfIIIJV) oxides that reoxidize Cr(II1). This 4.6 year laboratory study tracked Cr and Mn redox transformations in soils contaminated with Cr(V1) which were then treated with different amounts of organic carbon (OC). Changes in Cr and Mn oxidation states within soils were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 48 publications
(57 reference statements)
0
17
0
Order By: Relevance
“…We have found in other column experiments that reduction by compost organic matter alone is comparatively short-lived (Aspray, unpublished). In terms of microbial reduction mechanisms, it is likely that Cr(VI) was reduced indirectly in the column by metabolic endproducts including Fe(II) and H 2 S [22,23]. Certainly the analysis of H 2 S in water samples (data not shown) during phase II sampling, suggests the presence of sulphate reducing bacteria and the possibility for indirect Cr(VI) reduction by this metabolic end-product.…”
Section: Discussionmentioning
confidence: 94%
“…We have found in other column experiments that reduction by compost organic matter alone is comparatively short-lived (Aspray, unpublished). In terms of microbial reduction mechanisms, it is likely that Cr(VI) was reduced indirectly in the column by metabolic endproducts including Fe(II) and H 2 S [22,23]. Certainly the analysis of H 2 S in water samples (data not shown) during phase II sampling, suggests the presence of sulphate reducing bacteria and the possibility for indirect Cr(VI) reduction by this metabolic end-product.…”
Section: Discussionmentioning
confidence: 94%
“…More recently, μ-XAS was used by McNear et al (2007) to identify Ni and Al layered double hydroxide phases in a soil contaminated by a Ni refinery and treated with lime. Tokunaga et al (2007) used Mn and Cr K-edge XAS to investigate the role of organic matter and soil Mn in the reduction and stability of Cr in contaminated soils. This study evidenced the importance of organic C availability and Mn redox status for the long-term stability of Cr reduction strategies for soil remediation.…”
Section: Assessment Of In-situ Techniques For the Remediation Of Contmentioning
confidence: 99%
“…Owing to the high surface charge density, various Mn oxides (e.g., including pyrolusite (β-MnO 2 ) and birnessite (δ-MnO 2 )) have been extensively as high efficient adsorbents to remove arsenic [ 14 , 15 , 16 , 17 ], nickel [ 18 , 19 ], lead [ 20 , 21 , 22 ], mercury [ 23 , 24 ], and chromium [ 25 , 26 , 27 ]. It is demonstrated that birnessite has hexagonal layer symmetry and may possess a variable number of octahedral cationic vacancies within their layer, which provides the abundant strong adsorption sites for heavy metals [ 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%